2015
DOI: 10.1097/shk.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Prediction of Mortality and the Need for Life-Saving Interventions in Trauma Patients Using Standard Vital Signs With Heart-Rate Variability and Complexity

Abstract: The goal of this study was to determine the effectiveness of using traditional and new vital signs (heart rate variability and complexity [HRV, HRC]) for predicting mortality and the need for life-saving interventions (LSIs) in prehospital trauma patients. Our hypothesis was that statistical regression models using traditional and new vital signs would be superior in predictive performance over models using standard vital signs alone. This study involved 108 prehospital trauma patients transported from the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Reduced HRV has been previously observed and reported by us [13,15,16] and by many other authors that have investigated patients in coma with brain lesions of different etiologies [6, 7, 10-12, 14, 18, 21, 26]. Several studies have demonstrated the potential utility of HRV as an indicator of mortality in intensive care unit patients [24,25,[28][29][30][31][32], and also as an indicator of prediction of lifesaving interventions in patients with trauma [22,[33][34][35][36][37]. However, to our knowledge, this study is the first reporting this issue by applying a novel method for the analysis of HRV indices, the so called Hilbert-Huang method, that has been developed for the digital processing of signals that contain non-Gaussian, nonlinear or non-stationary processes, as is the case of the cardiac R-R tachograms, from which are derived the HRV indices [63,68,69,74,[91][92][93] Significant differences have been found of HRV indices between survivors and nonsurvivors in several studies.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Reduced HRV has been previously observed and reported by us [13,15,16] and by many other authors that have investigated patients in coma with brain lesions of different etiologies [6, 7, 10-12, 14, 18, 21, 26]. Several studies have demonstrated the potential utility of HRV as an indicator of mortality in intensive care unit patients [24,25,[28][29][30][31][32], and also as an indicator of prediction of lifesaving interventions in patients with trauma [22,[33][34][35][36][37]. However, to our knowledge, this study is the first reporting this issue by applying a novel method for the analysis of HRV indices, the so called Hilbert-Huang method, that has been developed for the digital processing of signals that contain non-Gaussian, nonlinear or non-stationary processes, as is the case of the cardiac R-R tachograms, from which are derived the HRV indices [63,68,69,74,[91][92][93] Significant differences have been found of HRV indices between survivors and nonsurvivors in several studies.…”
Section: Discussionmentioning
confidence: 68%
“…It has been shown that the ANS functional state predicts responsiveness in disorders of consciousness [5]. Multiple indices of HRV calculated in the time, frequency or informational domains have been studied in patients in coma with different objectives: to assess brainstem dysfunction [6], to assess brain death [7][8][9], differentiation of autonomic nervous activity in different stages of coma [10], diagnosis of dysautonomia after traumatic brain injuries (TBI) [11], calculation and description of HRV indices of patients in coma [12] correlation of the HRV parameters with the Glasgow coma score (GCS) [13][14][15][16], prediction or prognosis of the outcome in TBI, acute cerebral vascular disease, or critically ill neurosurgical patients [17][18][19][20][21][22][23], association of HRV indices with mortality in patients with TBI [24][25][26][27][28][29][30][31][32], and prediction of life saving interventions in patients with trauma [22,[33][34][35][36][37].…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Warning indices and notification systems that use physiological measurements to produce comprehensive metrics of patient health [3,4] and identify patterns predictive of patient instabilities [5,6] are a promising tool to provide lead time prior to a critical event when effective mitigations can be taken [7]. A sampling of such methods include approaches for identifying need for life-saving interventions in trauma patients [8,9], patients at risk for septic shock in the intensive care unit [10], need for care escalation from step-down units [1113], and potential heart failure in at-home monitoring [14,15] environments. Patient monitoring environments are known for the number of false alarms [16,17], presenting a need to balance the performance of any new monitoring index and warning system to provide timely warnings prior to an event and low false-alarm rates.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies however have examined the relationship between pre-operative heart rate variability and post-operative outcome [29]. Our observations therefore add a new temporal dimension (the intraoperative period) to the previously published data indicating that markers of autonomic dysfunction may serve as clinically useful tools in the evaluation and management of the critically ill [30][31][32][33].…”
Section: Discussionmentioning
confidence: 60%